The Healing Encounters and Attitudes Lists (HEAL): Psychometric Properties of a German Version (HEAL-D) in Comparison With the Original HEAL - Gerger, Heike; Buergler, Sarah; Sezer, Dilan; Grethler, Marc; Gaab, Jens; Locher, Cosima (Frontiers in Psychiatry, 2020)
Over the last years, the interest in understanding health improvements that occur due to non-specific treatment effects, rather than in response to the specific active treatment ingredients, increased. Nevertheless, investigations on patients’ idiosyncratic perspectives on the non-specific aspects of the healing encounter or of the treatment itself that contribute to placebo effects are still rare. The Healing Encounters and Attitudes Lists (HEAL) offer a unique and parsimonious set of instruments to measure patients’ views on a variety of non-specific aspects of the caring encounter. The HEAL items can be administered as computerized adaptive tests (CATs) or short forms that assess the patient-provider connection, the healthcare environment, treatment expectancy, positive outlook, spirituality, as well as attitudes towards CAM. So far, no German version of the HEAL exists. The original 168 HEAL items were translated into German (HEAL-D) applying a translation-back-translation procedure. We examined the psychometric properties of HEAL-D in a sample of 165 participants who reported at least one health care visit during the last year. The German short forms of HEAL (HEAL-D-SF) showed good internal consistency and test-retest reliability. The factor structure observed in the English original items showed low to moderate model fit in our sample. The development of a German version of HEAL in addition to the original English items offers new possibilities for investigating patients’ idiosyncratic perspectives on the non-specific aspects of treatments across language borders. We will close with presenting possible clinical application as well as promising and relevant future research directions using HEAL-D-SF, including for instance large-scale, cross-national investigations.